Biaxial flexural strength of zirconia: A round robin test with 12 laboratories - Spintzyk, Sebastian; Geis-Gerstorfer, Jürgen; Bourauel, Christoph; Keilig, Ludger; Lohbauer, Ulrich; Brune, Annike; Greuling, Andreas; Arnold, Christin; Rues, Stefan; Adjiski, Ranko; Sawada, Tomofumi; Lümkemann, Nina; et al. (Dental Materials, 2021)
Objective: The aim of this interlaboratory round robin test was to prove the robustness of the DIN EN ISO 6872:2019 and to identify the influence of processing and testing variations. Methods: Each of the 12 laboratories participated (A–L) received 60 (n = 720) assigned zirconia specimens. All participants seperated the specimens from the blanks, sintered them, polished half of all specimens and performed the biaxial flexural test (DIN EN ISO 6872:2019). The surface roughness was determined by using tactile measuring device. Fractographic examination was performed under scanning-electron-microscopy (SEM). Data was analysed using Kolmogorov–Smirnov-, Kruskal–Wallis-, Mann–Whitney-U-test and two-parametric Weibull statistic (p < 0.05). Results: The results for both preparation methods (as-fired and polished) showed significant differences for some participants. The values for as-fired groups ranged between 513 (I) and 659 (E) MPa. H showed higher Weibull modulus than C, E and I. Within polished groups flexural strengths values from 465 (L) to 1212 (E) MPa were observed, with a tendency to clustered groups A, I, J, L (465–689 MPa) and remaining groups (877–1212 MPa). E presented the highest and H the lowest Weibull modulus. Within A and J, no impact of the preparation method on flexural strength values was observed. Within L, as-fired specimens showed higher flexural strength than polished ones. The flexural strength increase did only associate to a certain extent with measured surface roughness. Fractography showed defect populations depending on polishing techniques, associated to the strength level, especially for polished groups. Reduced strength is related to machining defects, regardless of the surface state. Significance: DIN EN ISO 6872:2019 can be seen as guidance to biaxial flexural strength testing but additional effort is necessary to ensure interlaboratory comparability. Calibrated furnaces and reliable sintering conditions are mandatory requirements together with detailed specifications on finishing or polishing procedures. Biaxial flexural testing is really a matter of understanding specimen preparation, alignment and mechanical testing by itself. DIN EN ISO 6872:2019 should further recommend reporting of mean surface roughness along with any biaxial flexural strength data. Fractography is a mandatory tool in interpretation and understanding of strength data.
CRIS-Team Scopus Importer:2021-01-29
Keywords: 5Y-PSZ; Flexural strength; ISO 6872; Surface quality; Translucent zirconia; Weibull statistics